Analisis Potensi Kecelakaan Kerja di PT. XYZ dengan Menggunakan Metode Hazard and Operability Study - Sokhibi, Akh.; Dwiyulianto, Moh Agung; Asri, Vikha Indira (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Electricity is a major economic factor in Indonesia. Providing electric power is divided into three processes, namely generation, transmission and distribution. PLN is one of the electrical energy providers in Indonesia which plays an important role in providing sufficient electricity for daily activities, industry and other sectors. K3 is an important factor that must be applied to PLN because it is related to electricity. The Transmission and Substation Service Unit (ULTG) carried out time-based maintenance, condition-based maintenance and emergency maintenance and it was found that one of the workers was not using complete Personal Protective Equipment (PPE) when checking the Lightning Arrester (LA). So research is needed with the aim of analyzing K3 in the activity process to determine potential hazards and hazard risk levels. Descriptive research methods are used to analyze the risk of work accidents that may occur during maintenance. This research uses the Hazard and Operability Study (HAZOP) method to determine the value of possibilities and consequences by distributing questionnaires to K3 supervisors. PT. A B C. The results show six hazards with a high risk level, one hazard with a medium risk level, and six hazards with a low risk level. High risk caused by material, electrical voltage and work attitude. Risk controls include testing equipment and PPE several times a year, refilling PPE, complying with SOPs, and providing drinking water. Hazard control efforts at PT. ABC includes the use of the HAZOP method, implementation of clear SOPs, provision of appropriate PPE, routine equipment checks, and emergency response plans in emergency situations.